2001
DOI: 10.1051/animres:2001101
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of cereal grains by orange pulp and carob pulp in faba bean-based diets fed to lambs: effects on growth performance and meat quality

Abstract: -Fourteen weaned lambs (43 days of age) were divided into two equal groups of seven animals and received two different diets. The experimental diet contained 10% of carob pulp and 10% of orange pulp associated to 54% of faba bean. The control diet contained 12% of maize meal and 12% of barley meal associated to 49.2% of faba bean. Both diets were pelletted and given ad libitum. The two diets had comparable contents of dry matter, ash, crude fat, fibre and crude protein. Control diet was relatively higher in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
4
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 16 publications
3
25
4
1
Order By: Relevance
“…Cooking loss values, which were within the range of 23.94 to 39.18% reported by Omojola and Adesehinwa (2006) and Sobayo et al (2008), were not significantly (p>0.05) different among the treatments. In general, except for ECPM diets where few of the studied carcass characteristics parameters were affected, the non-significant differences between the control diet and the other two CPM diets confirms the previous study (Lanza et al, 2001) who demonstrated that inclusion 10% of alternative feedstuffs, orange pulp and carob pulp, did not impact carcass characteristics.…”
Section: Resultssupporting
confidence: 85%
“…Cooking loss values, which were within the range of 23.94 to 39.18% reported by Omojola and Adesehinwa (2006) and Sobayo et al (2008), were not significantly (p>0.05) different among the treatments. In general, except for ECPM diets where few of the studied carcass characteristics parameters were affected, the non-significant differences between the control diet and the other two CPM diets confirms the previous study (Lanza et al, 2001) who demonstrated that inclusion 10% of alternative feedstuffs, orange pulp and carob pulp, did not impact carcass characteristics.…”
Section: Resultssupporting
confidence: 85%
“…CP has been previously used as a high energy feed in ration for supporting growth and lactation of cattle. 22 A large number of the citrus by-products are suitable for inclusion in ruminant diets because of the ability of ruminants to ferment high fiber feeds in the rumen. 11 CP can be used in animal feeding either fresh or after ensiled or dehydrated.…”
Section: Figurementioning
confidence: 99%
“…The by-products with a major percentage of DM loss at 48 h were orange and lemon peels (89.8 and 86.0%, respectively) and broccoli (86.1%). It is reasonable to expect a good efficiency in ruminant degradation when the citrus byproducts are studied because these feeds are highly fermentable [5,17]. Also melon, boiled and fresh artichoke had high values (77.5, 73.0 and 65.0%, respectively).…”
Section: Dry Matter Degradationmentioning
confidence: 99%